Percepção e uso de tecnologias da informação e comunicação por psicoterapeutas - Hallberg, Sílvia Cristina Marceliano (2015)
The present study refers to a Master thesis presented at the Post-Graduation Program in Psychology of the Pontifical Catholic University of Rio Grande do Sul. The Master thesis is divided in th two studies about information and communication technologies (ICTs) and psychotherapy. The first study is a systematic literature review that aimed to describe the current scenario of scientific production on psychotherapy and ICT. The second study consisted on an empirical study based on a quantitative exploratory, descriptive and cross-sectional design which aimed to investigate the perception and use of information and communication technologies (ICTs) by psychotherapists. The findings suggest significant presence of ICTs in the personal life of psychotherapists but still some restrictions in what refers to professional use. These restrictions are more explicit when related to social networking sites. Clinicians do not have a clear position regarding the existing regulations about the provision of psychological services through ICTs. The development of quantitative, descriptive studies with national and random sample is suggested, in order to achieve a generalized description of the use of ICTs by psychotherapists. Also the development of qualitative design studies to foster a deeper understanding of this issue is encourage